Revisión y estimación de impactos en la salud pública en la cuenca baja del río Bogotá, debido a contaminación hídrica y atmosférica bajo diferentes escenarios de saneamiento (2016)
In this work, a review is made of the state of public health of the municipalities of the lower basin of the Bogotá River, considering among other different sanitation scenarios and the assessment and perception of the inhabitants regarding the contamination of the river. For this purpose, a detailed review was carried out of the previous studies regarding the Bogotá River, and of the public health reports prepared by the responsible authorities in each municipality. Based on surveys applied to the inhabitants of some municipalities in the lower basin, certain positions are determined regarding the contamination of the Bogotá River and the valuation of environmental services through the contingent valuation method. Likewise, the appropriate uses of water are determined for certain river sanitation scenarios, as well as an analysis of the conditions of land use and undeclared costs as a consequence of the contamination in the lower basin...